Neuromuscular, hormonal and molecular responses to heavy resistance training in strength trained men; with special reference to various resistance exercise protocols, serum hormones and gene expression of androgen receptor and insulin-like growth factor-I - Ahtiainen, J. (Studies in Sport, Physical Education and Health, 2006)
The present study was designed to obtain more information on mechanisms leading to muscle hypertrophy by determination of the effects of different heavy resistance exercise protocols on acute and chronic neuromuscular and hormonal resporises in previously strength trained young men. The present study also examined gene expression of androgen receptors and insulin-like growth factor I (IGF-I) to further understand the adaptation mechanisms to resistance tratintng, The present results suggest that increased resistance exercise intensity induced by the so-called forced repetitions (FR) exercise System may be beneticial for the development of muscle mass and muscle strength during strength training. However, FR led to increased recovery time after the exercise. The length of the rest periods (2 vs. 5 minutes) between die sets may not play an important role in the magnitude of acute resistance exercise-induced responses and long-term training adaptations. The findings indicate that serum testosterone concentrations may be of importance for training-induced muscle hypertrophy as well as for strength development of the trained muscles, Increased IGF-IEa and MGF mRNA expression due to heavy resistance exercise supports the concept that they may be related to regenerative processes after the exercise and therefore, contribute to training-induced muscle hypertrophy. Because the acute exercise-induced responses and the time needed for recovery may differ considerably between different loading protocols, there is a need to optimize the contents and die frequency of differeiit training sessions in order to create proper resistance training programs to match the individual requirements of trainers. The present findings further suggest that there may be several different ways to create exercise conditions leading to large acute hormonal resporises due to hypertophic type of resistance exercises, These results indicate a need to optimise the volume and/or intensity of resistance exercises to meet the level of adaptation of the neuromuscular and endocrine Systems in order to further increase muscle mass and strength.